A practical and interactive web-based software for online Qur'anic Arabic learning - Abdullah, Matin Saad; Rahman, M.M. Hafizur; Pathan, Al-Sakib Khan; Alshaikhli, Imad Fakhri Taha (The Institute of Electrical and Electronics Engineers, Inc., 2016)
The intent of this paper is to summarize and analyze the data and experience earned from a practical implementation of online language learning approach specifically targeted to Qur’anic Arabic learning. The foundation of this work is based on the fact that in the current world, almost 80% of the Muslims are non-native speakers/users of Arabic language. As a religious obligation, a part of the Arabic Qur’an must be memorized by each of them to recite during the formal prayers. While for native Arabic speaking people, it is relatively easy to understand, this approach of ours aims at achieving a level of understanding of the recited Arabic words even for the non-native users. The power of Information and communications Technology (ICT) is effectively used in this domain. The experience could be expanded to cover other language learning approaches;however, our Web-based software does have some solid rationale-base to make it specific for Qur’anic Arabic only.Alongside presenting the gained results, we provide necessary backgrounds, theoretical analysis and modeling, and details about the practical implementation of the prototype. We discuss the design of different natural language processing algorithms for analyzing the Qur’anic corpus in order to identify and extract frequently occurring common language patterns to automate the production of educational material for the system. We also present some feedback of the user community built around the initial prototype which serves as a framework for capturing requirements from the world-wide user base (for each iteration) which is an essential component for the design based research methodology of the work